(untitled) (Medical Forum Monthly, 2024)
Objective: To identify and treat the acute flaccid paralysis in interior of Sindh reported at PMCH Nawabshah. Design: Retrospective, with proper date and record. Place and Duration of Study: Medicine and ICU Department at Peoples Medical College Hospital Nawabshah from 31st January to 31st October 2009. Patients of all 3 medical units were involved in the study during this period. Patients and Methods: 50 patients with acute flaccid paralysis (AFP) were admitted in Intensive Care Unit of Peoples medical college Hospital Nawabshshah with support of all emergency measures and were evaluated. Results: 50 patients presented with AFP during study period. 40 were males and 10 were females. GBS was the leading cause of AFP. Majority of the patients were young, out come was excellent. 2 patients died due to respiratory failure. Conclusion: GBS is the leading cause of AFP in adults in interior of the Sindh while facilities for treatment are limited, which need to be extended in the hospitals situated in interior of Pakistan i.e. ICU and plasmopharesis.